2016
DOI: 10.1002/prot.25008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of imine reductase‐specific sequence motifs

Abstract: Chiral amines are valuable building blocks for the production of a variety of pharmaceuticals, agrochemicals and other specialty chemicals. Only recently, imine reductases (IREDs) were discovered which catalyze the stereoselective reduction of imines to chiral amines. Although several IREDs were biochemically characterized in the last few years, knowledge of the reaction mechanism and the molecular basis of substrate specificity and stereoselectivity is limited. To gain further insights into the sequence-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 46 publications
2
69
0
1
Order By: Relevance
“…More than 30 IREDs have been characterizeda s catalysing intramolecular asymmetric reductions of various cyclic imines. [8,11] The question of how proteins in nature evolve new function is of fundamental significance. [5 -7] In the course of establishing the IRED database (Imine Reductase Engineering Database;h ttp://ired.biocatnet.de/), we observed that most imine reductases are annotated as dehydrogenases.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…More than 30 IREDs have been characterizeda s catalysing intramolecular asymmetric reductions of various cyclic imines. [8,11] The question of how proteins in nature evolve new function is of fundamental significance. [5 -7] In the course of establishing the IRED database (Imine Reductase Engineering Database;h ttp://ired.biocatnet.de/), we observed that most imine reductases are annotated as dehydrogenases.…”
mentioning
confidence: 99%
“…[5 -7] In the course of establishing the IRED database (Imine Reductase Engineering Database;h ttp://ired.biocatnet.de/), we observed that most imine reductases are annotated as dehydrogenases. [8,11] The question of how proteins in nature evolve new function is of fundamental significance. [8] We and others have recently demonstratedt hat IREDs appear to be incapableo fr educing C=Ob onds.…”
mentioning
confidence: 99%
See 3 more Smart Citations